2015
DOI: 10.1186/s12873-015-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-6 level as an early marker of injury severity in trauma patients in an urban low-income setting: a cross-sectional study

Abstract: BackgroundTrauma is still the leading cause of death in many regions of the world. Severity scores have been developed to assist in management of trauma victims. Immune response to trauma has been known to positively correspond to the severity of trauma. Part of this response involves release of cytokines into blood circulation which promote the acute inflammatory response commonly seen after trauma. Studies have shown that IL-6 levels commonly correlate positively with the Injury Severity Score (ISS). The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…However, the measurement performed after these hours to be clinically insignificant. 38 There was a significant relation between the development of complications and 6-hour SP-D level in this study. Hospitalisation costs and duration of the patient who developed complications were increased.…”
Section: Discussionsupporting
confidence: 49%
“…However, the measurement performed after these hours to be clinically insignificant. 38 There was a significant relation between the development of complications and 6-hour SP-D level in this study. Hospitalisation costs and duration of the patient who developed complications were increased.…”
Section: Discussionsupporting
confidence: 49%
“…IL‐6, for example, which is perhaps the most well‐studied biomarker of trauma, is a pro‐inflammatory mediator which acts as a procoagulant , results in the release of acute phase reactants such as C‐reactive protein , causes a shift in chemokine production and induces proliferation of B and T cells . In terms of its use as a prognosticator, IL‐6 correlates positively with injury severity score (ISS) and extent of traumatic injuries , as well as with MODS . A few investigations found that levels of IL‐6 are higher in nonsurvivors of traumatic injury than survivors , thereby proposing its utility in predicting the end‐point of mortality.…”
Section: Chemokines and Cytokines As Prognostic Biomarkersmentioning
confidence: 99%
“…Alterations in local and systemic immune responses after severe trauma are recognized as a physiological reaction to restore homeostasis. The magnitude of these immunological changes correlates with the degree of local and systemic tissue damage [6,19].…”
Section: Pathophysiology Of Severe Traumamentioning
confidence: 99%
“…Given their similar clinical profiles, there may be more similarities between severe trauma and severe cases of SARS-CoV-2 than might initially be assumed. In this review, we will consider the notion that severe disease progression in SARS-CoV-2/Corona Virus Disease 2019 (COVID- 19) patients mimics disease mechanisms that occur in complicated courses of severe trauma.…”
Section: Introductionmentioning
confidence: 99%